Synthesis of anatase particles via morphological control of titanium glycerolate intermediate precursor - Yakaboylu, Gunes Alp; Keskinbora, Cigdem Ozsoy; Sahin, Yucel; Suvaci, Ender (ROYAL SOC CHEMISTRY, 2019)
Titanium glycerolate precursors were prepared from a novel starting material and using glycerol as a chelating ligand and solvent via a developed method. This method and optimization of process parameters provided morphology control, and rod-like anatase particles with a high surface area and large aspect ratio were synthesized.
Keywords: TIO2 NANORODS; ASPECT-RATIO; GLYCOLATE; ROUTE; CITRATE; FACILE; Chemistry; Crystallography